MODEL PENGEMBANGAN PENDIDIKAN PESANTREN; STUDY DI PONDOK PESANTREN AL- RASYID DANDER BOJONEGORO - Sumadi Sumadi (JP : JURNAL PENDIDIKAN, 2018)
Abstrak: This article describes the development of Al Rasyid Bojonegoro pesantren education as an effort to renew education in Indonesia. Educational development carried out by al-Rasyid pesantren lies in learning strategies, teaching materials, media and evaluation. All of this is used to support the success of the development of education in al-Rasyid pesantren. The results of observations made by the author can be explained that the development of al-Rasyid pesantren education consists of two things; the first is religious material which includes all Islamic religious studies and the study of classical or yellow books. Both material skills and life skills that cover a variety of fields and organizations. In this connection, according to the author's analysis, the model developed by al-Rasyid pesantren leads to the Intrumental Integration model. This is because pesantren with an instrumental integration model are pesantren that combine formal education with non-school education.Keywords: Education, Pesantren, Development.